An Investigation into the Benefits of Investing in Chinese Multinational Companies. (August 2018) - Berrill, Jenny; Sun, Shengkai
We provide a unique longitudinal analysis into firm-level multinationality of Chinese firms between 2002 and 2012 using two measures of multinationality—the Aggarwal, Berrill, Hutson and Kearney (2011, International Business Review, 20, 557–577) system and foreign sales as a percentage of total sales. We find that Chinese firms have low levels of multinationality with most foreign sales in the triad regions of Asia, Europe and North America. We use mean variance spanning tests to investigate the benefits from investing in Chinese multinational corporations (MNCs). We find that Chinese MNCs offer little diversification benefits to domestic investors and firms with greater multinationality levels do not result in greater benefits.